Frontispiece: Diarylethene Self‐Assembled Monolayers: Cocrystallization and Mixing‐Induced Cooperativity Highlighted by Scanning Tunneling Microscopy at the Liquid/Solid Interface. Issue 32 (23rd July 2015) - Frath, Denis; Sakano, Takeshi; Imaizumi, Yohei; Yokoyama, Soichi; Hirose, Takashi; Matsuda, Kenji
Abstract : Self‐Assembly The cooperative effects in the adsorption process at an octanoic acid/highly oriented pyrolytic graphite interface has been investigated by scanning tunneling microscopy for the three isomers of a diarylethene derivative. It was found that the annulated isomer has a very large equilibrium constant, which explains the predominantly observed ordering of the annulated isomer. The analysis using a cooperative model indicates the formation of mixed crystals and mixing‐induced cooperativity, providing a new view of the formation of 2D multicomponent molecular ordering. For more details see the Full Paper by K. Matsuda and co‐workers on page 11350 ff.